MAST CELLS CONTENT IN THE STRUCTURES OF THE ISCHEMIC MODEL WOUND ON THE 12TH DAY OF REGENERATIVE POTENTIAL STIMULATION BY AUTO- AND HETEROFIBROBLASTS AND DERMAL EQUIVALENT - Ye. Yu. SHAPOVALOVA; T. A. BOYKO; Yu. G. BARANOVSKIY; S. A. VASILENKO (Кубанский научный медицинский вестник, 2017)
Mast cell is a traditional cell for wound healing, but their content in the wound after transplantation of autoand heterofibroblasts and dermal equivalent on the basis of these cells remains poorly studied.Aim. To study the morphological structure, collagen formation, angiogenesis and content of mast cells in biopsy materials of the newly formed epidermis and dermis on the 12th day of their recovery in a model ischemic wound after administration of auto- and heterofibroblasts and after transplantation of dermal equivalent with heterofibroblasts.Materials and methods. The study was performed on 28 white mature mice of the C57 / B1 line aged up to 1 year. 0.4 ml of suspension with 1.33 million fibroblasts in growth medium DMEM F12 (Lonza) and in dermal equivalent were administered around and into the bottom of skin surgical model wound in the scapular region. The scar was embedded in paraffin and stained with hematoxylin and eosin, according to Weigert-Van Gieson, and kit for mast cells staining (Biovitrum).Results. On the 12th day epidermis is thicker after introduction of autofibroblasts, but it is more differentiated after transplantation of dermal equivalent with heterofibroblasts. Angiogenesis is also most active after the administration of autofibroblasts. Fibroblasts production of collagen fibers in granulation tissue, angiogenesis and the content of functionally active mast cells indicates the most favorable influence of autofibroblasts transplantation on the wound healing.Conclusion. The effect of dermal equivalent with heterofibroblasts differs from exposure autofibroblasts by several percent: the area of collagen fibers – by 2%, the area of blood vessels − by 5%, the index of degranulation of mast cells – by 4%.